2020
DOI: 10.2147/ijn.s259028
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electrospun Fibers Immobilized with BMP-2 Mediated by Polydopamine Combined with Autogenous Tendon to Repair Developmental Dysplasia of the Hip in a Porcine Model</p>

Abstract: Purpose Developmental dysplasia of the hip (DDH) can increase the pressure between the joints, which causes secondary hip osteoarthritis. The aim of the present study was to fabricate poly(D, L-lactic acid)-poly(ethylene glycol)-poly(D, L-lactic acid) (PELA) electrospun fibrous scaffolds, immobilized with bone morphogenetic protein-2 (BMP-2), to repair the acetabulum defects. Methods The characteristics of PELA electrospun were analyzed using scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…The electrospun scaffolds were prepared in keeping with a previously described method. 19 First, 0.5 g PELA (Bioruler) was completely dissolved in 1.5 g dichloromethane (Thermo Fisher Scientific) and 0.8 g dichloromethane methylformamide (Thermo Fisher Scientific) solvent. The mixture was stirred at room temperature overnight and transferred to a 1-mL syringe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrospun scaffolds were prepared in keeping with a previously described method. 19 First, 0.5 g PELA (Bioruler) was completely dissolved in 1.5 g dichloromethane (Thermo Fisher Scientific) and 0.8 g dichloromethane methylformamide (Thermo Fisher Scientific) solvent. The mixture was stirred at room temperature overnight and transferred to a 1-mL syringe.…”
Section: Methodsmentioning
confidence: 99%
“…The results confirmed that BMP-2 can be released continuously within 1 month and promote osteogenic differentiation of stem cells. 19 Although the electrospun scaffold has the potential to induce osteogenic differentiation of stem cells, the reconstructed tissue is not fully osteogenic differentiation, and most of the structure of the implant is still unknown.…”
mentioning
confidence: 99%
“…Cultured human bone marrow-derived mesenchymal stem cells (hMSCs) were well attached with minor cytotoxicity, Figure 3a. The study revealed a positive effect on the osteogenesis, the complete acetabular defects repair, Figure 3b, but also an incomplete bone formation which is influenced by the insufficient BMP-2 dose [95]. Several techniques were combined along with electrospinning to fabricate nHA/PLA/gelatin 3D scaffold.…”
Section: D Electrospun Structures For In Vivo Implantsmentioning
confidence: 99%
“…Inducing implant differentiation into cartilage and bone but also completely degraded without toxicity [35] LbL polymer microcapsule MnO 2 Eliminating hydrogen peroxide H 2 O 2 and protecting cells from oxidative stress [36] Exosomes miR-140, miR-9-5p, miR-100-5p, miR-135b, miR-1405p, and lncRNA KLF3-AS1 Reducing inflammation and promoting cartilage marker production [37][38][39][40][41] can transport small RNA molecules to cells and tissues.…”
Section: Bmp2mentioning
confidence: 99%